2016
DOI: 10.1155/2016/4370490
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Oxidase Activity in Type 2 Diabetes Mellitus Patients with and without Diabetic Peripheral Neuropathy

Abstract: This study investigated the relationship between serum xanthine oxidase (XOD) activity and the occurrence of diabetic peripheral neuropathy (DPN) in type 2 diabetes mellitus (T2DM) patients. Serum XOD activity, ischemia-modified albumin (IMA), uric acid (UA), albumin, glycated hemoglobin (HbA1c), advanced glycation end products (AGE), total free thiols, atherogenic index of plasma (AIP), and body mass index (BMI) were measured in 80 T2DM patients (29 with and 51 without DPN), and 30 nondiabetic control subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 35 publications
(49 reference statements)
3
44
0
2
Order By: Relevance
“…The possible active role of xanthine oxidase in oxidative stress in type 2 DM has not received sufficient attention. A few studies have demonstrated increased XO activity in such patients and showed a positive correlation with HBA1C levels in the ranges of respectively 7.1%‐9.3% in one study and 7.6%‐8.8% in the other . The HBA1C range in the 170 patients included in this meta‐analysis was 6.1%‐7.25% .…”
Section: Discussionmentioning
confidence: 69%
“…The possible active role of xanthine oxidase in oxidative stress in type 2 DM has not received sufficient attention. A few studies have demonstrated increased XO activity in such patients and showed a positive correlation with HBA1C levels in the ranges of respectively 7.1%‐9.3% in one study and 7.6%‐8.8% in the other . The HBA1C range in the 170 patients included in this meta‐analysis was 6.1%‐7.25% .…”
Section: Discussionmentioning
confidence: 69%
“…Xanthine oxidase is an enzyme that is involved in generation of ROS. Moreover, it has been shown that serum xanthine oxidase activity is directly associated with AGE levels . Zinc has capacity to inhibit production of this enzyme …”
Section: Possible Mechanistic Model Of Zinc In the Inhibition Of Agesmentioning
confidence: 99%
“…Our data is supported by a recent clinical study showing that serum XO levels are significantly increased in both type 2 diabetes mellitus patients with and without diabetic peripheral neuropathy in comparison to healthy controls. Xanthine oxidase activity was also directly correlated to the formation of AGEs in these patients [43].…”
Section: Discussionmentioning
confidence: 84%